Calopogonium Orthocarpum in Conservation Farming - Pandey, S. N. (Journal of Soil and Water Conservation, 2022)
Of the 9,357 sq. miles total area of Damo- dar Valley, Upper Damodar catchment com- prising of about 7,000 sq. miles is subjected to heavy erosion through water due to undulating topography, erratic rainfall distribution and faulty land management practices in the region. The average annual rainfall of this area is about 50 inches of which nearly SO per cent is received during the four months—June to September. Under the Soil and Climatic conditions of the Upper Damodar catchment, different types of vegetation are required for providing cover to the land under different uses and land capability classes. Considering the problems of this region there is a need for plants that can grow vigorously under the local soil and climatic conditions, produce a dense cover for covering the exposed land surface, withstand the erosive action of runoff water flowing at great velocities, maintain the soil fertility, have the capacity to maintain the stand for a prolonged period, produce forage for the livestock and have the capacity to regenerate through seeds as well as vegetatively.